Cellular Tolerance, Accumulation and Distribution of Cadmium in Leaves of Hyperaccumulator Picris divaricata - HU, Peng-Jie; GAN, Yuan-Yuan; TANG, Ye-Tao; ZHANG, Quan-Fang; JIANG, Dan; YAO, Nan; QIU, Rong-Liang (Pedosphere, 2012)
Knowledge of cellular metal homeostasis will provide a better understanding of the mechanisms involved in metal tolerance and hyperaccumulation in metal-hyperaccumulating plants. Energy dispersive X-ray spectrometry （EDS） was used to determine the localization of cadmium （Cd） in leaves of the Zn/Cd hyperaccumulator Picris divaricata which had a shoot Cd concentration of 565 mg kg-1 after 2 weeks of growth in solution culture supplying 10μ tmol L^-1 CdCl2. The results indicated that Cd was distributed mainly in the trichomes, upper and lower epidermis and bundle sheath cells, with a relatively low level of Cd in mesophyll cells. Mesophyll protoplasts isolated from leaves remained viable after 24 h exposure to CdCl2 at a concentration up to 1 mmol L^-1, indicating their high tolerance to Cd. The intracellular Cd was visualized by staining with Leadmium Green dye, a cellular permeable Cd fluorescence probe. The results showed that the majority of protoplasts （〉 82%） did not accumulate Cd, with only a minority （〈 18%） showing Cd accumulation. In the Cd-accumulating protoplasts, Cd accumulation was depressed by the addition of Fe^2＋, Mn^2＋ and the metabolic inhibitor carbonyl cyanide m-chlorophenylhydrazone （CCCP）, but not by Ca^2＋ or Zn^2＋. Furthermore, the entire process of Cd uptake from external solution into the cytoplasm and subsequent sequestration into vacuoles was successfully recorded by confocal images. These results suggested that reduced cellular Cd accumulation and efficient Cd vacuolar sequestration in mesophyll cells might be responsible for cellular Cd tolerance and distribution in the leaves of P. divaricata.